A Call for Biomonitoring Systems in Latin America and the Caribbean: Considerations for Potentially Toxic Metals/Metalloids. Issue 1 (14th September 2022) - Tamayo-Ortiz, Marcela; Riojas-Rodríguez, Horacio; Téllez-Rojo, Martha M.; Boischio, Ana; Mañay, Nelly; Menezes-Filho, José Antonio; Queirolo, Elena I.; Cortés, Sandra; Kordas, Katarzyna
The Latin America and the Caribbean (LAC) region makes up 8.4% of the world's population. Human biomonitoring (HBM) programs, which can shed light on population-level exposure to environmental contaminants such as toxic metals and thus, improve the health of the populations are inexistent in LAC countries. We call for the creation of HBM programs in the region and identify three viable design options for HBM at the individual level, through national surveys, newborn blood collection, and biobanks. We highlight some of challenges to the implementation of HBM programs, including financial and human resources, technical constrains (laboratory), sample, and data logistics. Finally, we provide the case studies of Brazil, Chile, Mexico, and Uruguay, to illustrate a range of responses to toxic metal exposure in non-occupational populations. Although different in many respects, the individual country responses share two commonalities: 1) academic centers drive the research to raise awareness of governmental entities; 2) reference levels are adapted from international norms rather than arising from the studied populations. Well-designed and sufficiently funded biomonitoring systems need to be established in each country of the LAC region. HBM programs are key to promoting human health by informing the public and contributing to policy processes that establish sustainable environmental controls and health prevention programs.